E-government Implementation in Calamba Water District and Public Trust: Basis for Enhancement Program - Espiel, Abby Mae (Journal of Interdisciplinary Perspectives, 2024)
The research comprehensively analyzed the relationship between the e-government implementation of Calamba Water District (CWD) and the level of public trust among the concessionaires. It also delved into the challenges faced by concessionaires in utilizing CWD e-government services and the factors influencing their trust in its implementation. The study employed a descriptive-correlational design and surveyed 397 CWD concessionaires in Calamba, Laguna, who had internet access and were actively engaged with CWD e-government services. Data collection was facilitated using a carefully selected research instrument and was analyzed using statistical treatments including simple mean, Four-point Likert Scale, standard deviation, and Pearson r. The research revealed a significant correlation between CWD's e-government implementation and the level of public trust among concessionaires. Specifically, the study revealed a substantial link between the level of e-government implementation in terms of ICT infrastructure, online services communication, human capital, privacy and security risks, ease of use, and usefulness of e-government services and public trust level among the concessionaires in terms of information, service, system quality, technology, and the government institution. It indicated that the higher the level of e-government implementation, the higher the public trust level among the concessionaires. Based on these findings, the study recommended an enhancement program to improve various aspects of the current e-government implementation of Calamba Water District. The proposed program focuses on addressing privacy and security risks, enhancing the user-friendliness of CWD e-government services, improving service quality related to ICT infrastructure and online communication, and enhancing the competency of CWD personnel. These enhancements are expected to bolster the overall program and ultimately increase public trust among concessionaires.